Delft Pneumatic Bipeds - Wisse, Martijn; Linde, Richard Q. van der.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Walking is simple for most of us, but two-legged robots (bipeds) are often slow, complex, inefficient, heavy, and have robotic-looking motions. What makes human walking so graceful? Can this be replicated with human-like robots? Martijn Wisse and Richard Q. van der Linde provide a detailed description of their research on pneumatic biped robots at the Delft University of Technology, The Netherlands. The book covers the basic theory - passive dynamic walking - and explains the implementation of pneumatic McKibben muscles in a series of successful prototypes.
Passive Dynamic Walking -- Baps; Pneumatic Actuation -- Mike; How to Keep from Falling Forward -- Max; Adding the Upper Body -- Denise; Sideways Stability -- Discussion and Future Research Directions.
Keywords: Engineering; Artificial intelligence; System theory; Control engineering; Robotics; Mechatronics; Engineering; Control, Robotics, Mechatronics; Artificial Intelligence (incl. Robotics).; Systems Theory, Control; Electronic books